PSYCHIC TENSIONS OF THE MAIN CHARACTERS IN WINTON’S CLOUDSTREET - Syarifah Fakhrana Fildzah; Herawati Abbas (JURNAL ILMU BUDAYA, 2022)
This research attempts to exposure the journey of psychic tensions of Sam, Dolly, and Rose, three of the main characters in Cloudstreet. In this regard, the researcher analyzes the causes of psychic tensions that are experienced by those main characters. By using the mother-child concepts the researcher attempts to see how the characters develop their selves through their relationship inside the family, primarily with the mother. The researcher finds that the root cause of psychic tensions and idiosyncratic behaviors of Sam, Dolly, and Rose is the result of an unsatisfying relationship between mother and children in their early childhood. Therefore, their unsatisfying relationship with their mother affects their behavior in their adulthood.